A THREE-PRONG STRATEGIC APPROACH TO SUCCESSFUL DISTANCE LEARNING DELIVERY - Scarafiotti, Carol (Online Learning, 2003)
Rio Salado College, headquartered in Tempe, Arizona, is nationally recognized as a role model for innovation and excellence in online education and as the “college of choice” for adults who balance their studies with work and family. One of the ten Maricopa Community Colleges, Rio Salado College has had a distance learning program since its inception in 1978. This paper describes a systems approach to the growth of successful online programs, using data for continuous improvement.